2018
DOI: 10.1080/14756366.2018.1533822
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel 6,7-dimethoxy-4-anilinoquinolines as potent c-Met inhibitors

Abstract: HGF/c-Met signalling pathway plays an important role in the development of cancers. A series of 6,7-dimethoxy-4-anilinoquinolines possessing benzimidazole moiety were synthesised and identified as potent inhibitors of the tyrosine kinase c-Met. Their in vitro biological activities against three cancer cell lines (A549, MCF-7, and MKN-45) were also evaluated. Most of these compounds exhibited moderate to remarkable potency. Among them, compound 12n showed the most potent inhibitory activity against c-Met with I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The cyclopropane-1,1-dicarboxiamide framework interferes with the Phe 1223 of the DFG motif, determining the disruption of the catalytic conformation (from DFG-in to DFG out) and the reorganization of the activation loop, which almost entirely envelops the ligand ( Figure 4 a). In the cavity the reoriented Phe 1223 forms a π-π stacking with the central fluorophenyl ring, the quinoline nitrogen links with a hydrogen bond the backbone amide of Met 1160 and also the dicarboxamide moiety forms additional hydrogen bonds with Lys 1110 and Asp 1222 ( Figure 4 b) [ 30 , 31 , 32 ].…”
Section: Quinolines As Inhibitors Of Carcinogenic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The cyclopropane-1,1-dicarboxiamide framework interferes with the Phe 1223 of the DFG motif, determining the disruption of the catalytic conformation (from DFG-in to DFG out) and the reorganization of the activation loop, which almost entirely envelops the ligand ( Figure 4 a). In the cavity the reoriented Phe 1223 forms a π-π stacking with the central fluorophenyl ring, the quinoline nitrogen links with a hydrogen bond the backbone amide of Met 1160 and also the dicarboxamide moiety forms additional hydrogen bonds with Lys 1110 and Asp 1222 ( Figure 4 b) [ 30 , 31 , 32 ].…”
Section: Quinolines As Inhibitors Of Carcinogenic Pathwaysmentioning
confidence: 99%
“… ( a ) crystal structure of kinase domain of c-Met in complex with foretinib (PDB ID: 3LQ8). In the box the binding cavity of the receptor occupied by the quinoline small molecule is illustrated (the activation loop is represented with transparent surface) [ 31 ]; ( b ) interactions of foretinib with amino acid residues of the c-Met active site [ 32 ]. …”
Section: Figurementioning
confidence: 99%
“…Molecular docking, molecular dynamics, and virtual screening approaches can now be efficiently used for the design of new inhibitors of the MET kinase domain [27,56,[76][77][78][79][80]. From all these approaches, new potent compounds were obtained and more highlights revealed about MET kinase domain conformational behavior.…”
Section: Discussionmentioning
confidence: 99%
“…[108] The benzimidazole-quinoline hybrids possessed considerable antiproliferative activity, and among them, hybrid 52 (IC 50 : 6.1-13.4 µM, MTT assay) was comparable to cabozantinib (IC 50 : 4.5-11.8 µM) against A549, MCF-7, and MKN-45 cancer cell lines. [109][110][111][112] Molecular docking study demonstrated that hybrid 52 could bind tightly with the active site of c-Met by various interactions, so this hybrid could serve as a promising candidate for the development of novel c-Met inhibitors.…”
Section: Miscellaneous Benzimidazole Hybridsmentioning
confidence: 99%